Clean intermittent catheterization in patients with spinal cord injury: knowledge of nurses (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Introduction: Spinal cord injury results in failure to empty the bladder, leaving the individual exposed to the risk of recurrent urinary tract infection, vesicoureteral reflux and even loss of renal function. Clean intermittent catheterization (CIC) is the method of choice for emptying the bladder in these cases. Although it has a simple technique, its performance should be well oriented in order to avoid complications such as infections or traumas. Guidance for the technique should be performed during the hospitalization period due to the injury and the nurse is responsible for this action. Objective: To evaluate the knowledge of nurses working in a trauma care hospital in relation to clean intermittent catheterization. Methods: Questionnaire constructed based on the guidelines of the European Association of Urological Nurses, applied to 18 nurses from a university hospital, a reference in the treatment of spinal trauma, regarding neurological dysfunction of the lower urinary tract and clean intermittent catheterization. Results: The participants presented expressive knowledge about lower urinary tract neurological dysfunction and CIC. There were errors regarding the CIC technique in the indication of the use of procedure gloves, in the lubrication of the catheter, collection of periodic urine cultures, use of antibiotics and in the need for instructions before discharge from hospital. Conclusion: Although the sample demonstrated knowledge on several issues related to the subject, the errors indicate the need for training and especially awareness of the responsibility of guidance before discharge from hospital.